2019
DOI: 10.1021/acs.analchem.9b04718
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Bioanalyses with Capillary Electrophoresis

Abstract: This report covers advances in capillary electrophoresis (CE) from January 2018 through September 2019. A summary of the literature during this time period is insightful. A search performed using the SciFinder Scholar® database for journal reports (limited to English) using the term capillary electrophoresis returned approximately 1,800 publications. Further analysis of this list, depicted in Figure 1, provided a snapshot of activity in biomolecular research. Classes of biomolecules most frequently associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 234 publications
1
47
0
Order By: Relevance
“…Newly discovered analyte-interacting reagents or solvents, such as synthetic receptors, affinity probes, and ionic liquids, have been broadening the scope of analytes addressable by CE. We anticipate more exploration of such reagents will be continued to develop CE solutions for challenging analytes [8].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly discovered analyte-interacting reagents or solvents, such as synthetic receptors, affinity probes, and ionic liquids, have been broadening the scope of analytes addressable by CE. We anticipate more exploration of such reagents will be continued to develop CE solutions for challenging analytes [8].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…For the works published before 2018, many elegant reviews can be found [2,[4][5][6]. Notably, exciting CE applications in analysis of proteins, pharmaceuticals, nucleic acids, metabolites, and carbohydrates, have been thoroughly discussed in a nice review recently published [8], which also provides an outlook for future directions towards improving the analysis of single cells and bio-particles. Thus, in this review, we mainly covered emerging and evolving advances in the aspects of sample preconcentration, separation media or coating development, detector construction, and multidimensional separation.…”
Section: Introductionmentioning
confidence: 99%
“…Another common approach is to chemically modify the channel surface to reduce interaction of proteins with the wall. For two relatively recent reviews that address the role of protein adsorption in ME and CE separations, see [39,40]. The application of a high voltage to each reservoir is achieved by the presence of platinum electrodes directly connected to power supplies, while a persistent buffer flow is directed towards both sample and waste reservoirs [35].…”
Section: Microchip Electrophoresis: Technical Characteristics and Basmentioning
confidence: 99%
“…Another common approach is to chemically modify the channel surface to reduce interaction of proteins with the wall. For two relatively recent reviews that address the role of protein adsorption in ME and CE separations, see [39] and [40].…”
Section: Microchip Electrophoresis: Technical Characteristics and Basmentioning
confidence: 99%
“…Despite great potential and many years of work on MSS methods themselves, the analysis of streams, i.e. the central element of MSS, was underdeveloped until recently [8][9][10][11][12][13][14][15][16][17]. We developed a set of tools for the quantitative characterization of streams in MSS to fill in this gap [18,19].…”
Section: Introductionmentioning
confidence: 99%